Reestructuración técnico administrativa de la empresa Zapatos Pilin R.C (2018)
In the present work of degree, the technical and administrative restructuring of the company Shoes Pilin was developed by means of the application of the diagnosis, technical study, administrative study and financial study, within which the different actions and strategies for the development of The organization, based on the factors identified in the development of the diagnosis such as strengths, weaknesses, threats and opportunities, could identify the different aspects to be improved and implemented since through the technical study the production process was improved and they developed the tools that allow the optimization of the functioning of the productive system such as: the technical files, diagrams of processes and operations, study of capacity and times. On the other hand, through the administrative study, the strategic planning elements that the company lacked, such as mission, vision, objectives, goals and management indicators, were designed.